Congratulations, it’s a risk factor! Varied social determinants of health at different ages of becoming a parent in Canada - Jordan MacDonald; David Speed (PLoS ONE, 2026)
Teen (<20 years of age) and young (<25 years of age) parents made up nearly 10% of new parents in Canada in 2023. Despite this, research on the socioeconomic and health outcomes of these young parents has declined significantly, alongside rates of young parenthood, over the past three decades. Current research on young parents often dichotomizes teen/young parenthood and/or excludes fathers from consideration. The present study addresses these two gaps by modelling age of parenthood as a continuous, nonlinear predictor and by including both mothers and fathers. Using 2017 Statistics Canada General Social Survey ( N = 6,282), we examined the associations between age of parenthood (age that an individual became a parent) and current education, self-rated health, self-rated mental health, life satisfaction, personal income, and household income. We expected that the earliest age of parenthood would be associated with significantly poorer outcomes, which would rapidly improve as age of parenthood increased, plateauing around the mid- to late-20s. Most hypotheses were supported: age of parenthood had a non-linear association with nearly all outcomes. Individuals who had their first child before the ages of 26 to 31 were significantly more likely to report lower income, poorer education, and lower self-rated health and mental health. These associations were nonlinear, and the associations of becoming a parent at 19 is comparable to 20. Further implications are discussed.